(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Today, the global annual volume of excimer laser correction (ELC) is estimated to be 3.6 million procedures. Dry eye syndrome (DES) is a complication of ELC for myopia, and the frequency of DES at 1 month and 6 months after ELC for myopia has been reported to be 60% and 20%, respectively. Purpose: To assess the early and late impact of ELC for myopia on the development of DES. Material and Methods: Sixty-eight myopic patients (136 eyes) were prospectively divided into two groups, group 1 (a Laser-Assisted in Situ Keratomileusis (LASIK) group) and group 2 (a FemtoLASIK group). Patient age ranged from 20 to 44 years. Patients were assessed for DES (ocular surface, tear production, and tear film stability) preoperatively and postoperatively. Patients of group 1 received thin-flap LASIK using the Alcon Wavelight EX500 excimer laser. A 110-µm corneal flap was created by a Carriazo-Pendular microkeratome in group 1 and by an Alcon FS200 femto laser in group 2. Follow-up duration was 12 months. Results: Preoperative function tests showed mild dry eye in some patients of both groups. At 1 month and 3 months after ELC, the frequency of DES increased in group 1 by 75.5% and 63%, respectively, and in group 2, by 76.5% and 64.9%, respectively. At 6 months, the frequency of DES decreased in groups 1 and 2 by 38.7% and 40%, respectively, compared to the 3-month time point. However, 10% of the patients showing no signs of DES preoperatively had persistent DES after ELC. Conclusion: First, the baseline frequency of DES in patients with myopia was 10%. Second, at 1 month and 3 months after ELC for myopia, the frequency of DES increased by 75.5% and 63%, respectively, in the LASIK group, and by 76.5% and 64.9%, respectively, in the FemtoLASIK group. In addition, the frequency did not depend on the laser technique. Third, we noted a gradual decrease in the frequency of DES at late time points after ELC for myopia. At 6 months, the frequency of DES decreased by 38.7% and 40% in groups 1 and 2, respectively, compared to the 3-month time point. Finally, 10% of the patients showing no signs of DES preoperatively had persistent DES after ELC for myopia.